2011
DOI: 10.1089/scd.2010.0355
|View full text |Cite
|
Sign up to set email alerts
|

Low Doses of Bone Morphogenetic Protein 4 Increase the Survival of Human Adipose-Derived Stem Cells Maintaining Their Stemness and Multipotency

Abstract: Mesenchymal stem cells (MSCs) have emerged as important tools for cell therapy; therefore, identification of factors capable of governing their ex vivo expansion become essential. In this study we demonstrate that human adipose-derived stem cells (ASCs) express all components of the bone morphogenetic protein (BMP)/BMP receptor signaling pathway and respond to BMP4 inducing upregulated expression of its specific target genes Id1-Id4. Moreover, ASCs grown in a medium reduced in serum produce endogenous BMP4 tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…This finding was inconsistent with other studies that demonstrated no effect 16, 57 or even a positive effect 43 of BMP4 on OPC proliferation. However, recent studies have suggested that the effects of BMP4 on stem cell proliferation are dose‐dependent; low dose BMP4 increases proliferation, but high dose BMP4 decreases proliferation of mesenchymal stem cells 53 or primordial germ cells 31. Considering that OPC proliferation is also affected by many factors, BMP4 may have dose‐dependent and opposite effects on OPC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was inconsistent with other studies that demonstrated no effect 16, 57 or even a positive effect 43 of BMP4 on OPC proliferation. However, recent studies have suggested that the effects of BMP4 on stem cell proliferation are dose‐dependent; low dose BMP4 increases proliferation, but high dose BMP4 decreases proliferation of mesenchymal stem cells 53 or primordial germ cells 31. Considering that OPC proliferation is also affected by many factors, BMP4 may have dose‐dependent and opposite effects on OPC proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…BMP-2, BMP-6, and BMP-14 are considered as major factors in osteogenic differentiation of ASCs s [148,149]; whereas, BMP-7 promotes both chondrogenesis as well as osteogenesis [150]. The osteogenic potential of ASCs is affected by the concentration of BMP and nature of differentiation medium [151,152,153]. A notable osteogenesis promoting effect of combined retinoic acid and BMP2 in murine ASCs have also been evidenced [154].…”
Section: Characterization Of Ascsmentioning
confidence: 99%
“…The usage of low-serum containing culture media supplemented with recombinant growth factors [e.g., epidermal growth factor, plateletderived growth factor and/or basic fibroblast growth factor] has been described [79][80][81][82] . Low doses of bone morphogenic protein 4 have also been shown to stimulate ASC proliferation [83] . Nevertheless, the gold standard for culturing ASCs will be a medium absolutely free from animal serum or factors, with well-known ingredients [7] .…”
Section: Specific Differences and Culture Standardizationmentioning
confidence: 99%